Voices from Syrian Minors as Refugees: Expectations from the International Community - Demir, Selcuk Besir (Springer, 2020)
Syria has been afflicted with a civil war that has turned into a humanitarian and refugee crisis. Millions of people have had to leave their homes to find safer places to survive. This recent refugee crisis has been considered as a serious social phenomenon that should be scrutinized using a scientific lens to understand what is being experienced by the victims of the war. In this respect, this qualitative study aims to investigate why the civil war in Syria broke out and why it still continues. The article also discusses the expectations of Syrian refugee minors from the international community. The refugees expect the international community to solve their long-standing problems and challenges. The results of the study revealed that Syrian minors expect the international community to solve their problems including inadequate access to health services and educational opportunities, food and accommodation, and forced child marriage. In addition, Syrian minors were found to be unaware of potential ways to overcome difficulties and seek solutions for the problems they suffer from.
Keywords: Conflicts; Syrian civil war; Minors; Expectation of international community; Refuges studies